Peningkatan Kompetensi Paedagogik Guru Mata Pelajaran Melalui Supervisi Akademik Berkelanjutan di SMKN 2 Praya Tengah - Akhirman Bakri (UNDIKMA, 2021)
The purpose of this study was to improve the pedagogic competence of subject teachers through continuous academic supervision at SMKN 2 Praya Tengah. The research method used in this research is school action research. This research consists of two cycles consisting of planning, implementation, supervision, and reflection. The data collection techniques in this study were documents, observations, and checklists, while the data analysis techniques used descriptive analysis. The results showed that the teacher's pedagogic competence increased from cycle to cycle. In the pre-cycle the average value of the pedagogic competence of 14 teachers was 52%, in the first cycle the number of teachers who made the syllabus was 31% and the lesson plan was 31%. in the second cycle there was an increase in the number of syllabus 83% and teacher lesson plans 89%, so that the competence of teachers in compiling the syllabus and lesson plans increased to 58%, thus through academic supervision could increase the pedagogic competence of subject teachers.